Syntactic parsing: where are we going? - Lopes, Lucelene; Pardo, Thiago Alexandre Salgueiro; Duran, Magali S. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2024)
In this review & opinion paper, we discuss the options and challenges for syntactic parsing. Despite significant advances in recent years, driven primarily by neural network architectures, parsing accuracy appears to be approaching a plateau. This paper proposes a reflection on the factors that may possibly be influencing such results and suggests some future paths.